Teologis Killen & Beer, dan Whitehead (International Forum of Researchers and Lecturers, 2025)
Christian religious education plays an important role in shaping the faith and character of students so that they grow like Christ. However, an approach that overemphasizes the cognitive aspect often prevents students from experiencing faith in its entirety in everyday life. Theological reflection is present as an approach that can bridge the gap between life experiences and understanding of Christian faith. Killen and de Beer offer a practical method of theological reflection, emphasizing awareness of experience, the meaning of values, and interpretation based on sources of faith. Meanwhile, Whitehead emphasizes the dynamics between tradition, personal experience, and culture in shaping theological understanding. Both approaches make significant contributions to Christian religious education because they encourage students to not only know the teachings of faith, but also to live them in the context of real life. Thus, theological reflection can be a transformative method in Christian religious education, strengthening students' involvement in a meaningful and relevant faith learning process.